Internet Gaming Disorder and Psychological Distress: a PRISMA systematic review - Mustafa Can Gursesli; Andrea Guazzini; Ramita Thawonmas; Clara Valenti; Mirko Duradoni; Ruck Thawonmas (Heliyon)
Gaming can be considered both an adaptive and a maladaptive coping mechanism. In the latter case, Internet Gaming Disorder (IGD) could develop. IGD is a disorder recognized by ICD-11 and DSM-V in which the individual participates in gaming activities despite the negative aspects that may result, such as increased levels of psychological distress. The aim of this study was to evaluate the relationship between IGD and psychological distress through a systematic review based on the PRISMA guidelines. 2222 sources were found with the keywords “gaming disorder” and “psychological distress” in different databases (i.e., Google Scholar, PsycInfo, PsycArticles, PubMed, Science Direct, Sociological Abstracts, and Academic Search Complete). After applying inclusion and exclusion criteria, 66 studies were included in the review that confirmed a consistent association between IGD and psychological distress, and a narrative synthesis was conducted. Specifically, 42 studies employed correlational analyses, and 67 % of them reported effect sizes greater than r = 0.30 in the relationship between IGD and measures of psychological distress (including its key dimensions). Moreover, depression consistently showed the strongest positive association with IGD, followed by anxiety and stress. Furthermore, although the number of studies is not the same across the age groups, the strength of this relationship tends to increase with age. Specifically, young adults and adults demonstrate more robust effect sizes than adolescents and children. These findings support the concept of a bidirectional relationship between IGD and psychological distress, emphasising the need for prevention strategies targeted at specific age groups, as well as the need for further longitudinal research to clarify causality.